Comparison of granule and traditional decoction of Gancao Xiexin for cold-heat complex pattern recurrent oral ulcer: a randomized controlled trial - Liu, Si-Run; Zhu, Hai-Tao; Chen, Pei-Chi; Zeng, Yu-Yu; Wang, Rui-Min; Xu, Hua-Chong; Li, Ze-Jian (Frontiers in Pharmacology, 2026)
ObjectiveTo compare the clinical efficacy and metabolites of Gancao Xiexin Decoction (GXD) granules versus traditional decoction in patients with recurrent oral ulcers (ROU) and cold-heat complex syndrome.MethodsA randomized trial of 79 patients evaluated the clinical efficacy of both formulations for recurrent oral ulcers (ROU) with cold-heat complex syndrome. HPLC-ICP-MS was used to analyze metabolites and heavy metals.ResultsThe Traditional Chinese Medicine (TCM) group, granule group and biomedicine group all showed significant improvements in clinical efficacy, inflammatory factors, and immune markers (P < 0.05). However, no significant differences were found between granules and decoction in salivary inflammatory factors, immune indicators, pain VAS scores, or TCM syndrome scores (P > 0.05). HPLC-ICP-MS analysis showed 60.4% common peak ratio in decoction and 68.1% in granules, with significantly lower heavy metal levels (Cu, As, Cd, Hg, Pb) in granules (P < 0.01).ConclusionGXD granules and traditional decoction showed comparable clinical efficacy in managing ROU with cold-heat complex syndrome. Notably, granule formulations exhibited lower heavy metal content, suggesting potential advantages in safety profile.